2012
DOI: 10.1172/jci44421
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte iron regulates adiponectin and insulin sensitivity

Abstract: Iron overload is associated with increased diabetes risk. We therefore investigated the effect of iron on adiponectin, an insulin-sensitizing adipokine that is decreased in diabetic patients. In humans, normal-range serum ferritin levels were inversely associated with adiponectin, independent of inflammation. Ferritin was increased and adiponectin was decreased in type 2 diabetic and in obese diabetic subjects compared with those in equally obese individuals without metabolic syndrome. Mice fed a high-iron die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
304
9
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 279 publications
(341 citation statements)
references
References 82 publications
20
304
9
8
Order By: Relevance
“…Contrary to our findings, a number of other studies have indicated a positive association between serum adiponectin and measures of human iron stores 9, 37, 38. These studies may be limited by the choice of surrogate for HIC.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to our findings, a number of other studies have indicated a positive association between serum adiponectin and measures of human iron stores 9, 37, 38. These studies may be limited by the choice of surrogate for HIC.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies may be limited by the choice of surrogate for HIC. In those three studies, inverse correlations were noted between serum ferritin and serum adiponectin; however, this only reached statistical significance in two of the studies 9, 37. These are interesting observations that were not seen in our cohort.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations